How transformational leadership predicts employees' affective commitment and performance. Issue 9 (19th November 2018) - Ribeiro, Neuza; Yücel, İlhami; Gomes, Daniel
Abstract : Purpose: The purpose of this paper is to examine the impact of transformational leadership (TL) on employees' individual performance (IP) through the mediating role of affective commitment (AC). More specifically, it aims to understand how TL relates to employees' AC, TL relates to employees' IP, employees' AC relates to IP and employees' AC mediates the relationship between TL and employees' IP. Design/methodology/approach: A total of 476 Turkish healthcare professionals participated in this study. The mediation effect of AC in the relationship between TL and employees' IP was tested by structural equation modeling. Findings: The results indicate that AC mediates the relationship between TL and employees' IP. In others words, transformational leaders promote employees' AC which, in turn, increases their IP. Practical implications: This study suggests that organizations should select, develop and invest in leaders who adopt a TL style because they build a climate of admiration, loyalty, respect, participation and involvement for employees which will in turn enhance their commitment and performance. Originality/value: This study responds to calls for research studies to explore the mediating mechanism in the TL process (Judge et al., 2006), as the mediation effects explain the conditions in which TL is related to the favorable outcomes.